Flaubert et Zola : dix ans d’amitié - Alain Pagès (Flaubert: Revue Critique et Génétique)
Flaubert and Zola were friends for ten years, between 1869 and 1880. Their friendship was fruitful. It was characterized by a genuine intellectual exchange, despite some disagreements about the functions of literature. When Zola bought his house in Médan, on the banks of the Seine, he thought of the example of Croisset: the two men shared the same vision of an ideal literary retreat, conducive to writing.